2019
DOI: 10.1097/gox.0000000000002084
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Total Leg Fillet Flap to Cover Multiple Pelvic Pressure Ulcers

Abstract: Summary: The authors present the surgical strategy in the treatment of a morbidly obese paraplegic patient with a massive sacral pressure ulcer as well as bilateral trochanteric ulcers in a 1-step leg-sacrificing procedure utilizing the “spare-part” concept. It is the intention of the authors to reinforce the use of fillet flaps as a last resort option in paraplegic patients with pressure sores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 6 publications
0
8
0
1
Order By: Relevance
“…The advantage of fillet flap is offering secure cutaneous skin resurfacing, robust tissue for padding, pelvic stability resumption, and the obliteration of the dead space caused by pressure injuries. 8,9 These reconstruction goals help to achieve durable wound coverage, infection resolution, and daily life activity restoration. However, case series showed that the complication of the fillet flap procedure ranges from superficial skin necrosis, wound dehiscence, flap failure, to abscess formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantage of fillet flap is offering secure cutaneous skin resurfacing, robust tissue for padding, pelvic stability resumption, and the obliteration of the dead space caused by pressure injuries. 8,9 These reconstruction goals help to achieve durable wound coverage, infection resolution, and daily life activity restoration. However, case series showed that the complication of the fillet flap procedure ranges from superficial skin necrosis, wound dehiscence, flap failure, to abscess formation.…”
Section: Discussionmentioning
confidence: 99%
“…2 For patients with ischial and sacral pressure ulcers, temporary colostomy should be considered before fillet flap reconstruction. 9 Overall, the fillet flap technique provides a safe, secure, and single-staged way to manage end-stage pressure injuries in a paraplegic SCI patient. Its indications are (1) multiple or recurrent pressure injuries lacking adjacent tissue coverage, (2) extensive pressure injuries without satisfactory local or rotational flap, and (3) pressure injuries with severe hip and knee joint contractures resulting in nonfunctional lower limbs.…”
Section: Discussionmentioning
confidence: 99%
“…11). 59 Those cases often present with extensive osteomyelitis recalcitrant to antibiotic therapy and surgical débridement. It is difficult to convince the patient that amputation is the best option for treatment, even in the cases of nonfunctional limbs.…”
Section: Multiple Ulcersmentioning
confidence: 99%
“…En una revisión hasta 2016, realizado por McCarthy, 9 sólo había siete artículos que se referían a los colgajos en filete parciales o totales de la extremidad inferior para el cierre de úlceras de presión; sin embargo, en nuestra revisión, la cual abarca hasta 2019, solamente hay tres autores que utilizan prácticamente la totalidad de la extremidad inferior para el cierre de las úlceras complejas 2,7,8 que, como norma, abarcan úlceras de ambos lados de la línea media, es decir, coexisten úlceras derechas e izquierdas en el mismo paciente. Por lo tanto, se requiere de un colgajo que cubra la máxima longitud del defecto, usando como punto-pivote una de las caderas para alcanzar la otra.…”
Section: Wwwmedigraphicorgmxunclassified